Supply, demand and prices in the US housing market - Thomas Conefrey; Karl Whelan (University College Dublin, UCD School of Economics, 2013)
The slowdown in the US economy in 2008, and in the housing market in particular, has been accompanied by a sharp fall in house prices and a glut of homes for sale on the market. While the idea that this overhang of dwellings for sale should place downward pressure on house prices is intuitive, little empirical work has been done in this area. This paper explicitly models the relationship between changes in house prices and various measures of housing supply. The results show that months supply of new homes places greater downward pressure on house prices that the months supply of existing homes. We build a small simulation model to examine the evolution of the housing market.
Keywords: R21; R31; 330; Housing market; supply; prices